2016
DOI: 10.3390/w8050205
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological Evaluation of Lake Chad Basin Using Space Borne and Hydrological Model Observations

Abstract: Sustainable water resource management requires the assessment of hydrological changes in response to climate fluctuations and anthropogenic activities in any given area. A quantitative estimation of water balance entities is important to understand the variations within a basin. Water resources in remote areas with little infrastructure and technological knowhow suffer from poor documentation, rendering water management difficult and unreliable. This study analyzes the changes in the hydrological behavior of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 40 publications
1
36
0
Order By: Relevance
“…The lake recession in the second half of the 20th century has triggered conflicts related to food security, poverty, and migration [11,12]. It is therefore crucial to continuously monitor Lake Chad to increase our understanding of water resource availability.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lake recession in the second half of the 20th century has triggered conflicts related to food security, poverty, and migration [11,12]. It is therefore crucial to continuously monitor Lake Chad to increase our understanding of water resource availability.…”
Section: Introductionmentioning
confidence: 99%
“…The spatio-temporal characteristics of water storage change within the Lake Chad basin from 2003 to 2013 was investigated by Buma and Lee [15] using the Gravity Recovery and Climate Experiment (GRACE) and Landsat imageries. Additionally, Buma et al [12] investigated the diverse aspects of the Lake Chad basin through a combined used of updated remotely sensed and hydrological model datasets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Buma et al [20] assess observed changes in hydrological conditions of Lake Chad basin based on the total water storage (TWS) derived from GRACE, lake levels taken from satellite altimetry, and water fluxes and soil moisture obtained from the Global Land Data Assimilation System (GLDAS). The authors observe a similar pattern between TWS and lake level changes and subsurface water volume changes.…”
Section: Contributionsmentioning
confidence: 99%
“…This data is needed because the quantitative estimation of water balance components is important to understand the variations taking place at catchment/global level [2]. However, in many developing and arid regions of the world, the assessment and management of water resources is still a major challenge due to data scarcity [3].…”
Section: Introductionmentioning
confidence: 99%